Unpaid care work and social norms: Gender, generation and change in northern Uganda - Rost, L (2020)
There has been increasing interest in understanding care responsibilities in developing countries but there remains limited evidence on determinants of gendered participation in care. This thesis proposes social norms as an explanation for gender- and age-based differences in the time devoted to unpaid care work – including caring for people and domestic work. It investigates how social norms exert influence at different levels, why they are complied with and how they are contested and changing.